Toward new perspectives on the interaction of iron and sulfur metabolism in plants - Forieri, Ilaria; Wirtz, Markus; Hell, Rüdiger (Frontiers in plant science, 2013)
The deficiency of nutrients has been extensively investigated because of its impact on plant growth and yield. So far, the effects of a combined nutrient limitation have rarely been analyzed, although such situations are likely to occur in agroecosystems. Iron (Fe) is a prerequisite for many essential cellular functions. Its availability is easily becoming limiting for plant growth and thus higher plants have evolved different strategies to cope with Fe deficiency. Sulfur (S) is an essential macro-nutrient and the responses triggered by shortage situations have been well characterized. The interaction between these two nutrients is less investigated but might be of particular importance because most of the metabolically active Fe is bound to S in Fe–S clusters. The biosynthesis of Fe–S clusters requires the provision of reduced S and chelated Fe in a defined stoichiometric ratio, strongly suggesting coordination between the metabolisms of the two nutrients. Here the available information on interactions between Fe and S nutritional status is evaluated. Experiments with Arabidopsis thaliana and crop plants indicate a co-regulation and point to a possible role of Fe–S cluster synthesis or abundance in the Fe/S network.
Gesehen am 11.05.2017